Digital Transformation in Business Management: A Conceptual Review and Its Implications for Modern Organisations: Transformasi Digital dalam Manajemen Bisnis: Tinjauan Konseptual dan Implikasinya terhadap Organisasi Modern - Fauzi, Ahmad; Kusuma , Kumara Adji (Indonesian Journal of Law and Economics Review, 2025)
This study aims to conceptually examine the dynamics of digital transformation in business management and its implications for the structure and capabilities of modern organizations. Digital transformation extends beyond technology adoption; it entails fundamental changes in organizational culture, leadership, and corporate strategy. Employing a qualitative approach, this research applies a narrative literature review method, analyzing 35 selected international scholarly journals across relevant disciplines. The findings indicate that successful digital transformation is strongly influenced by adaptive organizational culture and visionary digital leadership. The COVID-19 pandemic has acted as a catalyst, accelerating digitalization across core business processes. However, resistance to change and structural unpreparedness remain key obstacles faced by many organizations. The implications of this study underscore the importance of integrating digital strategy with culturally informed change management and promoting digital literacy across all organizational levels. This research contributes conceptually to the development of sustainable digital strategies grounded in the realities of modern organizational contexts. Highlights: Digital transformation requires cultural shifts, not just technology adoption. Visionary leadership and digital literacy are critical to success. COVID-19 accelerated transformation, but many firms remain structurally unprepared. Keywords: digital transformation, organizational culture, digital leadership, business strategy, modern organization